(untitled) (University Arena, 2025)
Physical training and sport education in schools, high schools and universities is essential due to its biological character with positive effects and benefits from educational, social and cultural perspective. Through various forms of practice, physical training and sport involves emotional side of personality, contribute in strengthening the body and spirit, stimulates creativity, will of affirmation, inclusion in group, team building an development and evolution of students personality. Since antiquity latins affirmed: “Mens sana in corpore sano!” meaning: Healthy mind in a healthy body! Modern education in schools, high schools and universities should focus more on importance for students of physical training and sport, in addition to disciplines included in educational curricula since knowledge acquired is better integrated and applied by healthy and strong students. A great benefit for student’s health and education are the mandatory sport hours, part of the educational curriculum and pro-grams. Every student has to follow those classes, planned and performed through a variety of exercises, activities and sports like soccer, handball, volleyball or basketball. Accomplishing those classes, many students develop a spirit for competition and some of them also a passion for a sport or another. Nevertheless, the inter -schools competitions like “Cup of high schools” or universities competitions (such as Decathlon or Spartakiada) are opportunities for teenagers to taste the victory and performance. The teachers/instructors that select students with specific skills and abilities for a sport can foster the process of forming future champions in various sports or at least performers that become professionals athletes that could have a healthy and wealthy life.